2021
DOI: 10.1136/ijgc-2020-002343
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery followed by chemotherapy and olaparib maintenance in BRCA 1/2 mutated recurrent ovarian cancer: a retrospective MITO group study

Abstract: IntroductionThe role of cytoreductive surgery in the poly-ADP ribose polymerase inhibitors era is not fully investigated. We evaluated the impact of surgery performed prior to platinum-based chemotherapy followed by olaparib maintenance in platinum-sensitive BRCA-mutated recurrent ovarian cancer.MethodsThis retrospective study included platinum-sensitive recurrent ovarian cancer BRCA-mutated patients from 13 Multicenter Italian Trials in Ovarian cancer and gynecological malignancies centers treated between Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The logical question is whether the introduction of PARPi in the first-line setting would mitigate the role of secondary cytoreductive surgery or, on the contrary, further reinforce it. A retrospective MITO group study confirmed the positive role of secondary cytoreductive surgery before platinum therapy and olaparib maintenance in BRCAm patients 58. In this study, the PARPi was used in a relapsed setting rather than in the first line and so there are still some issues on surgery secondary to PARPi.…”
Section: How Might Parpi Impact Surgical Treatment?mentioning
confidence: 73%
See 1 more Smart Citation
“…The logical question is whether the introduction of PARPi in the first-line setting would mitigate the role of secondary cytoreductive surgery or, on the contrary, further reinforce it. A retrospective MITO group study confirmed the positive role of secondary cytoreductive surgery before platinum therapy and olaparib maintenance in BRCAm patients 58. In this study, the PARPi was used in a relapsed setting rather than in the first line and so there are still some issues on surgery secondary to PARPi.…”
Section: How Might Parpi Impact Surgical Treatment?mentioning
confidence: 73%
“…A retrospective MITO group study confirmed the positive role of secondary cytoreductive surgery before platinum therapy and olaparib maintenance in BRCAm patients. 58 In this study, the PARPi was used in a relapsed setting rather than in the first line and so there are still some issues on surgery secondary to PARPi. Nevertheless, the pattern of first recurrence under or after PARPi is frequently oligometastatic 59 and secondary cytoreductive surgery might play even a greater role in the post-PARPi era.…”
Section: How Might Parpi Impact Surgical Treatment?mentioning
confidence: 99%
“…Two issues were not addressed. Regarding the prognostic value of BRCA or homologous recombination deficiency status in the recurrent setting for selection for surgery, a recent retrospective MITO group study suggested that BRCA-mutated patients who were undergoing SCS followed by chemotherapy and maintenance with a PARP inhibitor had a better DFS and OS compared with those who did not receive surgery [ 23 ]. Moreover, our previous data have suggested a potential benefit of SCS for DFS compared with only chemotherapy, irrespective of BRCA status, in patients who are primarily not treated with a PARP inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory data from the MITO real-life experience have shown that patients with BRCA 1/2 in progression while on olaparib maintenance had a low response rate when re-exposed to a platinum-based therapy with an objective response rate of only 29.2% in patients with a platinum-free interval of more than 12 months 13. Other data from a retrospective Australian multicohort study found an objective response rate of 24.7% in 77 patients receiving chemotherapy after poly (ADP-ribose) polymerase inhibitors 14.…”
Section: Discussionmentioning
confidence: 99%